Leaf water content and water source partitioning reveal species-specific drought vulnerabilities in subtropical shrubs - Peng, Wenxi; Jiang, Bo; Chang, Leru; Luo, Zidong (Frontiers in Plant Science, 2025)
Hydraulic regulation of leaf water content and root water uptake underpins drought resistance in woody plants, yet these processes remain poorly quantified in humid forest shrubs. Here we explored drought vulnerability of two shrubs in a subtropical humid forest based on field measurements of soil water content (SWC), leaf water content (LWC), and isotopic compositions (δ2H and δ18O) of xylem and soil water. The results showed that during the drought in 2022, SWC within the 0–100 cm depth declined sharply, with severe soil water deficiency persisted for more than three months. Consequently, the two shrubs exhibited significant differences in LWC over time. During the drought, LWC declined 22.1% in L. polystachyus versus a more pronounced 35.2% drop in V. negundo compared to wet periods. Meanwhile, LWC was a useful predictor of drought vulnerability and exhibited a threshold-type response that distinguished individual plants at no risk from those at increasing risk of drought-induced canopy damage/dieback. Water stable isotopes revealed that L. polystachyus and V. negundo both mainly rely on shallow (0–30 cm) soil water (accounting for 58.8 and 70.5%, respectively) during wet period. However, it showed fundamentally divergent drought-response strategies during drought period: L. polystachyus enhanced drought resistance through progressive deep-water foraging (from 12.6% to 19.9%), while V. negundo maintained greater reliance on ephemeral shallow resources (accounting for 66.6%) and was thus more vulnerable. In addition, differences in SWC and plant size were important factors influencing plant water status and drought responses. These findings provide a useful framework to evaluate species differences in drought vulnerability regulated by water resource acquisition and plant size.